Polyphenols, their Metabolites and Derivatives as Drug Leads - Almeida, A. F.; dos Santos, Claudia Nunes; Ventura, Maria Rita (Current Pharmaceutical Design, 2018)
In this non-comprehensive review, the potential of natural polyphenols as lead compounds for the design and synthesis of new molecules with potential application in several diseases was highlighted. Organic synthesis has been essential for the development of new analogues of naturally found polyphenols, providing a wide range of structural modifications for structure-activity relationship studies and improving or modulating the biological activity of the promising compounds.
Keywords: Polyphenols